2015
DOI: 10.1371/journal.pone.0145810
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Wnt Genes Expressed in Neural Progenitor Zones during Zebrafish Brain Development

Abstract: Wnt signaling regulates multiple aspects of vertebrate central nervous system (CNS) development, including neurogenesis. However, vertebrate genomes can contain up to 25 Wnt genes, the functions of which are poorly characterized partly due to redundancy in their expression. To identify candidate Wnt genes as candidate mediators of pathway activity in specific brain progenitor zones, we have performed a comprehensive expression analysis at three different stages during zebrafish development. Antisense RNA probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 36 publications
4
35
0
Order By: Relevance
“…Pre-hybridization was performed for at least 2 hrs at 65°C. Probes used were fgfr1a, fgf3, fgf10a, and etv4 (Aman and Piotrowski, 2009), fgfr2 (Rohs et al, 2013), dld (Jiang et al, 2014), wnt2 (Poulain and Ober, 2011), wnt10a (Lush and Piotrowski, 2014b), wnt11r (Duncan et al, 2015), gfp (Dorsky et al, 2002), atoh1a…”
Section: In Situ Hybridization and Alkaline Phosphatase Stainingmentioning
confidence: 99%
“…Pre-hybridization was performed for at least 2 hrs at 65°C. Probes used were fgfr1a, fgf3, fgf10a, and etv4 (Aman and Piotrowski, 2009), fgfr2 (Rohs et al, 2013), dld (Jiang et al, 2014), wnt2 (Poulain and Ober, 2011), wnt10a (Lush and Piotrowski, 2014b), wnt11r (Duncan et al, 2015), gfp (Dorsky et al, 2002), atoh1a…”
Section: In Situ Hybridization and Alkaline Phosphatase Stainingmentioning
confidence: 99%
“…The function of NE in the regenerative condition and RG in both, physiological and regenerative conditions, are not well known. In the previous studies, we analyzed the function of Wnt signaling on adult neurogenesis in the optic tectum of zebrafish (Shitasako et al, ), and Wnt‐related genes were expressed in the central nervous system of the zebrafish embryo (Clements, Ong, & Traver, ; Duncan, Panahi, Piotrowski, & Dorsky, ; Hashimoto et al, ; Untergasser, Martowicz, Hermann, Töchterle, & Meyer, ). Moreover, other studies also showed that Wnt signaling regulates self‐renewal and differentiation of neural stem cells in the physiological and regenerative conditions in the retina, hypothalamus, and spinal cord (McPherson et al, ; Ramachandran, Zhao, & Goldman, ; Strand et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The function of NE in the regenerative condition and RG in both, physiological and regenerative conditions, are not well known. In the previous studies, we analyzed the function of Wnt signaling on adult neurogenesis in the optic tectum of zebrafish (Shitasako et al, 2017), and Wnt-related genes were expressed in the central nervous system of the zebrafish embryo (Clements, Ong, & Traver, 2009;Duncan, Panahi, Piotrowski, & Dorsky, 2015;Hashimoto et al, 2000;Untergasser, Martowicz, Hermann, T€ ochterle, & Meyer, 2011).…”
mentioning
confidence: 99%
“…38 Canonical Wnt in the roof plate in gnathostomes and tailbud in amphioxus, no data on lamprey. References: Gnathostomes; Mouse, Wnt1, Wnt3, and Wnt3a in the roof plate 39,40 ; Chick, Wnt1 and Wnt3a 41 ; Zebrafish, Wnt1 and Wnt3 in the roof plate, 42,43 Wnt3a in the tailbud. 44 Lamprey; data only on noncanonical Wnt5 which is expressed across the DV spinal cord.…”
Section: Patterning the Vertebrate Spinal Cord: The Ap Axismentioning
confidence: 99%